LEGITIMITY OF POLITICAL DECISIONS: THE ROLE OF THE REFERENDUM IN THE DEMOCRATIC PROCESS - Goleanu, Camelia-Elena (International Journal of Legal and Social Order, 2024)
The popular vote in Romania has a history that spans several decades in various political and social contexts. Starting from the initial forms of consultation of the population known as the plebiscite, at present, as a result of social and political evolution and transformations, we find the referendum regulated at constitutional level. The referendum is an important tool in the democratic process to allow citizens to speak directly on key issues affecting society. Through the referendum, citizens have the opportunity to participate actively in political decision-making, thereby strengthening the principles of the democratic state. This form of direct democracy gives citizens the opportunity to vote on specific issues such as revision of the constitution, impeachment of the president, adoption of important laws or topics of public interest. The role of the referendum is also to legitimize political decisions and to evaluate the mandates of elected representatives, which can lead to public debates that stimulate citizens' information and promote a better understanding of the problems faced by society. Referenda are therefore not only a voting tool, but also a means of civic education and strengthening social cohesion, with the potential to strengthen democracy and create a sense of belonging and responsibility among citizens. The Constitutional Court of Romania has a fundamental role in ensuring the legality and legitimacy of the referendum process, contributing to the protection of democracy and the fundamental rights of citizens. It helps to maintain a balance between political decisions, popular will and respect for constitutional norms.